THE DYNAMICS OF VORTEX OSCILLATION IN A SUPERCONDUCTOR - Butayev, Ruslan; Tailanov, Nizomiddin; Isayev, Nurbek (Журнал математики и информатики, 2021)
In this paper, we study the phenomenon of magnetic flux oscillations — the oscillation of vortex matter as a result of the thermomagnetic instability of a critical state in a superconductor. The spatial and temporal distributions of thermal and electromagnetic disturbances in a flat semi-infinite superconducting sample in the viscous flow regime with a linear current-voltage characteristic are studied.